2016
DOI: 10.1007/s10327-016-0644-0
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the prospects of Streptomyces sp. RP1A-12 in managing groundnut stem rot disease caused by Sclerotium rolfsii Sacc

Abstract: Stem rot of groundnut caused by the soilborne pathogen Sclerotium rolfsii can cause significant yield losses. Biological control of stem rot using actinomycetes is a viable alternative to existing fungicidal management. Though actinomycetes are prolific antibiotic producers, reports pertaining to their use in groundnut disease management are limited. Here, actinomycetes were isolated from groundnut rhizospheric soils and screened for antagonism against S. rolfsii through a dual culture assay. Culture filtrates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 43 publications
1
7
0
Order By: Relevance
“…In this study, none of the three tested isolates showed phosphate-solubilizing activity on NBRIP agar medium by establishing clear halo zones around the bacterial colony. Similar results were obtained by Jacob et al (2016), who showed promising findings from a GH (greenhouse) study, but the isolate was unable to demonstrate phosphate solubilizing activity.…”
Section: Indole-3 Acetic Acid (Iaa) Production and Phosphate Solubili...supporting
confidence: 82%
See 2 more Smart Citations
“…In this study, none of the three tested isolates showed phosphate-solubilizing activity on NBRIP agar medium by establishing clear halo zones around the bacterial colony. Similar results were obtained by Jacob et al (2016), who showed promising findings from a GH (greenhouse) study, but the isolate was unable to demonstrate phosphate solubilizing activity.…”
Section: Indole-3 Acetic Acid (Iaa) Production and Phosphate Solubili...supporting
confidence: 82%
“…This solution was incubated in the dark for 35 min. A change in colour from blue to orange showed a positive result for siderophore production (Jacob et al, 2016). Three replications were maintained, and uninoculated broth served as a control.…”
Section: Production Of Indole 3-acetic Acid (Iaa)mentioning
confidence: 99%
See 1 more Smart Citation
“…Although the high temperatures generated during composting are considered an important factor of sanitation, it seems that the above mentioned biotic factors can significantly influence the elimination or deactivation of harmful agents, not only during the composting process, but also after the application of compost as a substrate to soils as well. With the specific case of actinobacteria, the ability to produce compounds with useful features in pharmacology, agriculture and biotechnology is widely known [20]. These products are currently expensive, so consider the ability of actinomycetes producing interesting substances as siderophores or chitinases to promote plant growth and enhance antagonism to phytopathogens, opens new and sustainable possibilities.…”
Section: Resultsmentioning
confidence: 99%
“…rolfsii , S . sclerotiorum , and Botrytis cinerea [ 53 , 54 ]. Therefore, oxalotrophic isolates of S .…”
Section: Discussionmentioning
confidence: 99%